Trajectories of Union Renewal: Migrant Workers and the Revitalization of Union Solidarity in Saskatchewan - Stevens, Andrew (Labour / Le Travail, 2020)
Western Canada’s oil-exporting economies have come to rely on migrant labour as a cornerstone of economic development. A global division of labour intersecting with the constellation of Canada’s migrant worker programs has shaped the contemporary political-economic character of many Canadian provinces, including Saskatchewan. These programs have worked to construct bifurcated labour markets for growing low-wage industries that exist alongside high-wage resource-sector employment. Although a majority of these migrant workers end up employed in non-unionized workplaces, foreign workers who secure occupations in health care, construction, warehousing, and manufacturing are often represented by a union. The study explores union attitudes and union-member engagement among migrant labour through the lens of union revitalization, in an attempt to confront claims that migrant workers are without an affinity to organized labour and avoid participating in union business and the collective-bargaining process.